Teleworking, a triangle of perceptions: Managers, workers and family members - Pérez-Campdesuñer, Reyner; Sánchez-Rodríguez, Alexander; García-Vidal, Gelmar; Martínez-Vivar, Rodobaldo (Revista Venezolana de Gerencia, 2023)
Teleworking requires changes in the previous practices associated with its actors: managers, workers and family members. Not being able to assimilate these changes can affect the satisfaction of each one and generate a set of unfavorable effects in the different roles. In this research, through a survey applied to 321 participants from nine Ecuadorian provinces, assuming an infinite population and ensuring a researcher error of less than 10%, the level of satisfaction of the three roles analyzed was characterized with respect to a group of associated variables. As a result, it can be argued that although telework generates benefits for workers and employers, it requires changes in management methods and provokes different attitudes in the family environment. Regarding managers, although they recognize teleworking as viable, they perceive that their traditional control methods require changes to assume new practices and must be based on higher levels of trust and the development of a results-oriented function. With respect to workers and their families, they recognize that teleworking gives them a set of facilities, although it could affect family relationships and become a source of stress that affects health.